Failure Factors of Medical Students in Private and Public Sector Medical Colleges of Peshawar, Khyber Pakhtoonkwa: Failure Factors of Medical Students - Khan, Marina; Sajjad, Palwasha; Zeb, Aalia; Aurangzeb, Usama; Hussain, Sajid; Shah, Tayyiba (Pakistan Journal of Health Sciences, 2024)
In the medical world, stress and anxiety are very communal to manage educational affairs. Motivation is a failure among medical students is a very crucial point of discussion. Objective: To find factors that led to failure of medical students in public and private sector medical colleges. Methods: Qualitative approach was adopted for this cross-sectional study. Fourteen in depth interviews were carried out. Purposive sampling was implemented for this study that included medical students who failed in any one year of their medical journey, of public and private sector medical colleges in Peshawar. Results: Out of total interviewed participants, 64% of the respondents were female while 36% of the respondents were males. Amongst the total respondents, 71% were from private medical colleges whereas, 29% were from public medical colleges. 79% of respondents wanted to continue with same profession whereas 21% of respondents did not wanted to continue with their medical profession. Three main factors were observed that lead towards failure of medical students in public and private medical colleges. These factors include lack of peer support, instructor’s teaching attitude and pressure from institute and family. Conclusions: This study identified lack of peer support, instructors’ teaching attitude, and pressure from the institute and family as primary factors leading to the failure of medical students in public and private colleges in Peshawar. Despite these challenges, 79% of students remain motivated to continue their medical careers